Identification of single nucleotide variant in Mx1 gene associated with antibody response to Avian Influenza virus in Aseel chickens: SNP in Mx1-gene for antibody response to AIV in Aseel - Majeed, R; Zahoor, I; Anjum, A; Ali, M; Basheer, A (Journal of the Hellenic Veterinary Medical Society, 2023)
Aseel birds are known for their hardiness, thermotolerance, pugnacity, and robustness. However, they are highly susceptible to Avian Influenza (AI) and Newcastle Disease (ND) viruses which cause huge mortalities. Present study was designed to identify polymorphisms in exon-14 of Mx1, and 5’UTR & intron-7 of ROBO2 gene associated with antibody response to AIV (H9N2) and ND virus respectively in adult Aseel birds. After screening of 500 birds for HI-based antibody response against both viruses, two separate set of 40 birds, one for each virus, were selected on the basis of maximum divergence in their antibody response. The sequence data of exon-14 of Mx1 gene revealed 3 SNP, and that of ROBO2 gene showed 2 SNPs in intron-7 and 1 in 5’UTR. The genotypic frequencies of identified variants were tested for goodness-of-fit and only Mx_810 showed significant difference. The results of association analysis revealed a non-synonymous SNP (G>A), Mx1_567, significantly associated with pre- (P<0.01) and post-vaccination (P<0.01) antibody response against AIV. The LSD results showed that homozygous mutant (AA), and heterozygous (AG) genotypes had significantly greater values of pre- and post-vaccination antibody response compared with wild-type genotype. However, no SNP in the ROBO2 gene was found significantly associated with antibody response.